Kedudukan Investor Asing Saat Pengambilan Keputusan dalam Usaha Patungan (Joint Venture) Sesuai Peraturan Perundang-Undangan Indonesia - Peter Yordan Pangidoan Silitonga (UNES Law Review, 2023)
Investment in the era of globalization cannot be separated from a series of international agreements. Joint venture agreement in the context of foreign investment in Indonesia is the first step to form a joint venture which is required for foreign investors who plan to invest in Indonesia. The joint venture agreement sets out the objectives and policies of the joint venture company which can be used to interpret the agreements made by the company with its partners. Based on the description above, the author is interested in conducting research on How is the regulation regarding the position of foreign investors when making decisions in joint ventures in Indonesia? And How is the supervision carried out by the government on foreign investment in accordance with the regulations governing it? This research uses normative juridical method with literature study using secondary data. The result of this research is a Joint Venture company established in the form of a limited liability company, the important thing about the relationship between foreign investors and national investors who become majority shareholders and minority shareholders lies in the GMS which is subject to Law No. 40 of 2007 concerning Limited Liability Companies, if referring to the Law, basically shareholders in a limited liability company have no power in the management of the company, shareholders do not interfere in the management of the company.